Alternative methodology for chitin/hydroxyapatite composites using ionic liquids and supercritical fluid technology - Silva, Simone Santos (2013)
An alternative, green method was used to develop chitin-based biocomposite (ChHA) materials by an integrated strategy using ionic liquids, supercritical fluid drying, and salt leaching. ChHA matrices were produced by dissolving chitin in 1-butyl-methylimidazolium acetate along with salt and/or hydroxyapatite particles and then subsequent drying. The ChHA composite formed had a heterogeneous porous microstructure with 65%–85% porosity and pore sizes in the range of 100–300 µm. The hydroxyapatite was found to be well distributed within the composite structures and had a positive effect in the viability and proliferation of osteoblast-like cells, in vitro. Our findings indicate that these ChHA matrices have potential applications in bone tissue engineering.